Ukubuyisa Isidumbu – “Bringing back the body”: An examination into the ideology of vengeance in the Msinga and Mpofana rural locations(1882-1944) - Clegg, Jonathan (My University, 1979)
This paper attempts to shed some light on the 'inter-tribal faction fighting' which has rocked the Msinga and Mpofana rural locations for many decades. In this examination I have chosen to investigate the Tembu/Mabaso - Tembu/Majozi disturbances of 1922 because they have a long history which is fairly well documented and more importantly, the 1922 disturbances were a watershed in the relationship between tribes in Msinga and set a precedent for other tribes in the area with similar land problems and boundary disputes. Most importantly I think the war provided a model for local level politics among the districts within each tribe and was an important contribution to the development of a 'feud'( 1 ) ideology in Msinga. Thirdly the war effectively broke Terabu dominance in Msinga politics and paved the way for the Chunu people to consolidate their power base and influence among those tribes which had been at loggerheads with the Terabu. The final blow to the Tembu power came in 1944 when they were defeated in massive clashes with the Chunu. The Chunu's slowly assumed the leadership role in Msinga after this and their chief SiMakade, has now been elected by the KwaZulu government to represent all the other chiefs in Msinga at important KwaZulu government functions. The first section deals with a vast period of history and is necessarily brief in sections. Whereas the first section deals with the 'inter-tribal' wars between the major tribes in Msinga, the second section deals with a new phenomenon which starts appearing in the early 1930's - warfare between districts of the same tribe and even more stunning, fighting between sections within a single district within the same tribe. This breakdown of tribal cohesion into territorial opposition between districts and subsections within districts goes hand in hand with development of what I have called the 'ideology of vengeance' in Msinga. ( 2*) In the pages that follow I think it will become clear that in trying to understand the conditions under which this new social phenomenon developed, there is among all the other numerous factors, a single underlying element which seems to pervade the fighting at every level - the problem of insufficient land.
African Studies Seminar series. Paper presented May, 1979